En Bloc Arch Reconstruction With the Frozen Elephant Trunk Technique for Acute Type a Aortic Dissection - Liu, Penghong; Wen, Bing; Liu, Chao; Xu, Huashan; Zhao, Guochang; Sun, Fuqiang; Zhang, Hang; Yao, Xingxing (Frontiers in Cardiovascular Medicine, 2021)
Objective: The study objective was to evaluate the effect of en bloc arch reconstruction with frozen elephant trunk (FET) technique for acute type A aortic dissection. Methods: 41 patients with acute Stanford type A dissection underwent en bloc arch reconstruction combined with FET implantation between April 2018 and August 2020. The mean age of the patients was 46 ± 13 years, and 9 patients were female. One patient had Marfan syndrome. Six patients had pericardial tamponade, 9 had pleural effusion, 5 had transient cerebral ischemic attack, and 3 had chronic kidney disease. Results: The hospital mortality rate was 9.8% (4 patients). 2 (4.9%) patients had stroke, 23 (56.1%) had acute kidney injury, and 5 (12.2%) had renal failure requiring hemodialysis. During follow-up, the rate of complete false lumen thrombosis was 91.6% (33/36) around the FET, 69.4% (25/36) at the diaphragmatic level, and 27.8% (10/36) at the superior mesenteric artery level. The true lumen diameter at the same three levels of the descending aorta increased significantly while the false lumen diameter reduced at the two levels: pulmonary bifurcation and the diaphragm. The 1-, 2-and 3-year actuarial survival rates were 90.2% [95% confidence interval (CI), 81.2–99.2], 84.2% (95% CI, 70.1–98.3) and 70.2% (95% CI, 42.2–98), respectively. Conclusions: In patients with acute type A dissection, en bloc arch reconstruction with FET technique appeared to be feasible and effective with early clinical follow-up results. Future studies including a large sample size and long-term follow-up are required to evaluate the efficacy.